Pembelajaran Menyajikan Pesan dalam Bentuk Vlog Siswa Kelas VIII SMP Negeri 3 Kota Gorontalo Tahun Pelajaran 2023/2024 - Wulandari Mustapa; Dakia N. Djou; Ulfa Zakaria (Departement of Mathematics Education, 2024)
This study aims to determine the learning process of presenting messages in the form of vlog-based advertisements and to find out the learning outcomes of presenting messages in the form of advertisements in the form of vlog-based advertisements of grade VIII students of SMP State 3 Kota Gorontalo Junior High School in the 2023/2024 academic year. It employed descriptive qualitative. The data collection techniques included observation, tests, and documentation. The data analysis involved reduction and presentation techniques.The results indicated that the learning process of presenting messages in the form of vlog-based advertisements went quite well. The learning outcomes of presenting messages in the form of vlog-based advertisements were considered successful. The highest score obtained was 91 by Group 3, primarily due to the aspects of video narration and video quality. Meanwhile, the lowest score obtained was 72 by Group 4. Therefore, in this study, three groups completed the task successfully, while one group did not. These results show that students are able to present messages in the form of advertisements and then make them in the form of vlogs.